Henry George's writings on the United Kingdom - Wenzer, Kenneth C. (Research in the history of economic thought and methodology ;, 2002)
Henry George's political economy has been hailed as one of the great contributions of American social criticism. His writings have, however, invited interpretation in contradictory fashion. Commentaries have used him to uphold laissez-faire social Darwinism allowing for the aggrandizement of money. Some on the left have regarded his ideology as calling for a co-operative commonwealth well beyond the intentions of the single-tax mechanism. And there are those who see him as having, in effect, written a new Declaration of Independence as powerful as that of 1776. Bringing to light his previously unavailable British writings would clear up some misunderstandings and also present the man and his ideas in a fresher historical context.